Efficacy and Safety of Botulinum Toxin Type A in Treating Patients of Advanced Age with Idiopathic Trigeminal Neuralgia - Jing Liu; Ying-Ying Xu; Qi-Lin Zhang; Wei-Feng Luo (Pain Research and Management)
Objective. To assess the therapeutic efficacy and safety of botulinum toxin type A (BTX-A) for treating idiopathic trigeminal neuralgia (ITN) in patients ≥80 years old. Methods. Selected patients n=43 with ITN, recruited from the neurology clinic and inpatient department of the Second Affiliated Hospital of Soochow University between August 2008 and February 2014, were grouped by age, one subset n=14 ≥80 years old and another n=29 <60 years old. Each group scored similarly in degrees of pain registered by the visual analogue scale (VAS). Dosing, efficacy, and safety of BTX-A injections were compared by group. Results. Mean dosages of BTX-A were 91.3 ± 25.6 U and 71.8 ± 33.1 U in older and younger patients, respectively t=1.930, p=0.061. The median of the VAS score in older patients at baseline (8.5) declined significantly at 1 month after treatment (4.5) p=0.007, as did that of younger patients (8.0 and 5.0, resp.) p=0.001. The median of the D values of the VAS scores did not differ significantly by group (older, 2.5; younger, 0; Z=−1.073, p=0.283). Two patients in each group developed minor transient side effects p=0.825. Adverse reactions in both groups were mild, resolving spontaneously within 3 weeks. Conclusions. BTX-A is effective and safe in treating patients of advanced age (≥80 years old) with ITN, at dosages comparable to those used in much younger counterparts (<60 years old).